HIV/AIDS‐related stigma, immediate families, and proactive coping processes among a clinical sample of people living with HIV/AIDS in Philadelphia, Pennsylvania. Issue 7 (7th August 2019) - Meanley, Steven; Yehia, Baligh R.; Hines, Janet; Thomas, Rosemary; Calder, Daniel; Carter, Bryce; Dubé, Benoit; Bauermeister, José A.
Abstract: People living with HIV/AIDS (PLWHA) engage in proactive coping behaviors to minimize the risk of interpersonal stigma. This study explores proactive coping processes in navigating HIV/AIDS‐related stigma within immediate families. Data for this study come from 19 one‐on‐one, qualitative interviews with a diverse, clinical sample of PLWHA in Philadelphia, PA. Thematic analysis indicated that participants continue to experience enacted, anticipated, and internalized forms of HIV/AIDS‐related stigma. Participants discussed status concealment and selective disclosure as proactive coping resulting from anticipated stigma and physical distancing as proactive coping motivated by internalized HIV/AIDS‐related stigma. Study findings demonstrate how living with a stigmatized condition can affect PLWHA social interactions with close networks like immediate families, specifically in eliciting stigma‐avoidant behaviors. Anti‐stigma efforts that educate immediate families to overcome stigmatizing attitudes and provide HIV‐positive family members with high‐quality social support should be coupled with efforts that target health‐promotive self‐management strategies for PLWHA.